The power of reversibility: regulating gene activities via tetracycline-controlled transcription - Schönig, Kai; Bujard, Hermann; Gossen, Manfred (Guide to techniques in mouse development ; B: Mouse molecular genetics, 2010)
Tetracycline-controlled transcriptional activation systems are widely used to control gene expression in transgenic animals in a truly conditional manner. By this we refer to the capability of these expression systems to control gene activities not only in a tissue specific and temporal defined but also reversible manner. This versatility has made the Tet regulatory systems to a preeminent tool in reverse mouse genetics. The development of the technology in the past 15 years will be reviewed and guidelines will be given for its implementation in creating transgenic rodents. Finally, we highlight some recent exciting applications of the Tet technology as well as its foreseeable combination with other emerging technologies in mouse transgenesis.
Gesehen am 27.06.2023